اتجاهات جديدة في السياسة المقارنة - المغيربي, د. محمد زاهي (Dirasat in Economics and Business, 1979)
The comparison process represents one of the main foundations in scientific research in the field of social sciences, and thus goes beyond the scope and limits of any branch of these sciences or any discipline.My side is Comparative studies are one of the approaches used by various social sciences such as history, sociology, and others..: In the field of political science, we find that comparison is one of the approaches used in the various branches of this science. We find comparative studies of parties and foreign policies of different countries and other studies. Comparative politics is the only field, within the fields of political science, that bears within its name the curriculum or the method used in the study within this field, which is the comparative curriculum. This assumes that the comparative process or the comparative curriculum becomes one of the important basic requirements in this field. (1)